Aspekte der Aneignung in Klaus Manns Gide-Rezeption - Ralph Winter (Recherches Germaniques)
Personal and professional exchange between André Gide and Klaus Mann were not really driven by mutual interest and yet Mann’s admiration for the older French writer has been a very productive aspect of his life and work. He published a certain number of essays on Gide as well as an extensive biography and, by doing so, he contributed to a wider spreading of Gide’s works and ideas in the German speaking world. Within these biographical writings traces of a clearly induvial, even identificational reception of Gide’s works can be observed and described. By intertextual participation and transformation (Lachmann), Mann even comes to an intellectual and formal appropriation of these works. This practice shows how individual ways of reception can influence French-German cultural transfer.